Dendritic morphology, synaptic transmission, and activity of mature granule cells born following pilocarpine-induced status epilepticus in the rat - Gao, Fei; Song, Xueying; Zhu, Dexiao; Wang, Xiaochen; Hao, Aijun; Nadler, J. Victor; Zhan, Ren-Zhi (Frontiers in Cellular Neuroscience, 2015)
To understand the potential role of enhanced hippocampal neurogenesis after pilocarpine-induced status epilepticus (SE) in the development of epilepsy, we quantitatively analyzed the geometry of apical dendrites, synaptic transmission, and activation levels of normotopically distributed mature newborn granule cells in the rat. SE in male Sprague-Dawley rats lasting for more than 2 hours was induced by an intraperitoneal injection of pilocarpine. The complexity, spine density, miniature post-synaptic currents, and activity-regulated cytoskeleton-associated protein (Arc) expression of granule cells born five days after SE were studied at least 10 weeks after CAG-GFP retroviral vector-mediated labeling. Mature granule cells born after SE had dendritic complexity similar to that of granule cells born naturally, but with denser mushroom-like spines in dendritic segments located in the outer molecular layer. Miniature inhibitory post-synaptic currents (mIPSCs) were similar between the controls and rats subjected to SE; however, smaller miniature excitatory post-synaptic current (mEPSC) amplitude with a trend toward less frequent was found in mature granule cells born after SE. After maturation, granule cells born after SE did not show denser Arc expression in the resting condition or after being activated by transient seizure activity than vicinal GFP-unlabeled granule cells. Thus our results suggest that normotopic granule cells born after pilocarpine-induced SE are no more active when mature than age-matched, naturally born granule cells.